Association Between Maternal Macronutrient Intake with Human Milk Oligosaccharides in Hispanic Mothers (P11-073-19). (13th June 2019) - Jones, Roshonda; Berger, Paige; Plows, Jasmine; Alderete, Tanya; Yonemitsu, Chloe; Bode, Lars; Goran, Michael
Abstract: Objectives: Studies have shown that maternal diet impacts the composition of breastmilk. One of the most abundant components of breastmilk are complex sugars collectively known as human milk oligosaccharides (HMOs) that, among other effects, act as prebiotics helping to shape the gut microbiota of infants. The aim of this study was to examine associations between maternal intake of macronutrients and abundance of individual HMOs in breastmilk up to 6 months postpartum, the recommended period of exclusive breastfeeding. Methods: Hispanic mothers provided a sample of their breast milk at 1 month (n = 130) and 6 months (n = 54) postpartum and dietary macronutrients were assessed at these timepoints using 24-hour diet recalls in duplicate or triplicate. Linear models were used to examine the 1- and 6-month cross sectional associations between saturated fat, unsaturated fats, protein, fiber, added sugar, total sugar and fructose and 19 of the most abundant HMOs measured by high-pressure liquid chromatography. All models adjusted for age, pre-pregnancy BMI, total caloric intake, number of breastfeedings per day and average duration of breastfeeding. Results: At 1-month postpartum, saturated fat intake was inversely associated with milk lacto-N-tetraose (LNT) ( p -value = 0.044) and positively associated with difucosyllacto-N-hexaose (DFLNH) ( p -value = 0.007). At 6-months postpartum, added sugar intake was negatively associated with fucosyl-disialyl-lacto-N-hexaose (FDSLNH) ( p -value = 0.001), and total sugar intake was also negatively associated with fucosyl-disialyl-lacto-N-hexaose (FDSLNH) ( p -value = 0.003). Conclusions: Our results indicate that the abundance of several HMOs is associated with maternal macronutrient intake. This finding is preliminary to determining the possible impact of maternal diet on the composition of infants' gut microbiota via HMOs. Funding Sources: National Institute of Diabetes and Digestive and Kidney Diseases (NIH R01 DK110793) and the Gerber Foundation.